2022
DOI: 10.1155/2022/3674931
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism and Lipidome Are Highly Regulated during Osteogenic Differentiation of Dental Follicle Cells

Abstract: Dental follicle cells (DFCs) are stem/progenitor cells of the periodontium and give rise to alveolar osteoblasts. However, understanding of the molecular mechanisms of osteogenic differentiation, which is required for cell-based therapies, is delimited. This study is aimed at analyzing the energy metabolism during the osteogenic differentiation of DFCs. Human DFCs were cultured, and osteogenic differentiation was induced by either dexamethasone or bone morphogenetic protein 2 (BMP2). Previous microarray data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…In conclusion, our study provides new information on the mechanisms of the later phase of osteogenic differentiation of DFCs. In connection with the results of our previous study [17], during this differentiation phase metabolic processes are induced in DFCs that increase oxidative stress that need to be regulated. It remains unclear to what extent the signaling pathways associated with the Rho-GTPases are involved in the differentiation and regulation of oxidative stress.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In conclusion, our study provides new information on the mechanisms of the later phase of osteogenic differentiation of DFCs. In connection with the results of our previous study [17], during this differentiation phase metabolic processes are induced in DFCs that increase oxidative stress that need to be regulated. It remains unclear to what extent the signaling pathways associated with the Rho-GTPases are involved in the differentiation and regulation of oxidative stress.…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies found that lipid synthesis (for example, of cholesterol) and other metabolic processes are also involved in the later stages of osteogenic differentiation (14 days after induction) [16, 17]. Moreover, inhibition of fatty acid synthesis decreased the osteogenic differentiation potential of DFCs [17]. The present study also shows that oxidative stress is induced during osteogenic differentiation.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Recently, induced pluripotent stem cells-derived MSC (iPSC-MSCs) has been proposed as an alternative resource. iPSCs generated with this pluripotent have numerous applications, including expansion to large scale cell numbers for tissue engineering and the development of cellular therapeutics [54][55][56]. Here, although MEFs cells derived from embryonic tissues show pluripotency, the exact mechanism remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%